Daily roosting behaviour of the critically endangered White-bellied Heron Ardea insignis as a function of day length. Issue 5 (4th May 2022) - Khandu, Pema; Gale, George A.; Kinley, Kinley; Tandin, Tandin; Shimano, Satoshi; Bumrungsri, Sara
ABSTRACT: The White-bellied Heron ( Ardea insignis ) is listed as a critically endangered bird species by BirdLife International due to the rapid population decline. Before this study, nothing was known about the night roosting behaviour of this imperiled species. Here, we report on the night roosting behaviour of the White-bellied Herons in Punatsangchhu and Mangdechhu river basins of Bhutan. There was a significant difference in landing and takeoff flights between the short- and long-day periods (P <0.05). Overall, the night roosting behaviour was dominated by sleeping (65 ± 11 min). We also documented two prominent behaviours that were thermoregulatory in function. The White-bellied Herons roosts solitarily on the tree branches in the night and makes extensive use of the night roosting trees. Therefore, night roosting trees are essential for consideration while assessing the home range size of the White-bellied Herons for their better conservation and management.